العوامل المؤثرة على عوائد محافظ قروض المصارف التجارية ( دراسة ميدانية على عينة من المصارف التجارية الخاصة في سورية ) - ميا, علي; عمار, قصي; محمد, رامي محمد (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف البحث إلى تحديد العوامل المؤثرة على عوائد محافظ القروض للمصارف التجارية الخاصة في سورية خلال الفترة ( 2007- 2012)، حيث تم دراسة سلوك المتغير التابع المتمثل في ( عائد محافظ القروض ) والمتغيرات المستقلة المتمثلة في( معدل توظيف الودائع في القروض، وحجم المصرف، والسيولة النقدية وعمر المصرف وعدد فروع المصرف، ومعدل كفاية رأس المال). خلص البحث إلى: وجود أثر معنوي إيجابي للمتغيرات المستقلة: لعمر المصرف ولمعدل كفاية رأس المال ( ما عدا مصرف بيبلوس سورية) على عوائد محافظ قروض المصارف التجارية الخاصة محل الدراسة. عدم وجود أثر معنوي ذات دلالة إحصائية للمتغيرات المستقلة: لمعدل توظيف الودائع في القروض، وحجم المصرف والسيولة النقدية ( ما عدا مصرف بيبلوس سورية )، وعدد فروع المصرف ( ما عدا مصرف سورية والمهجر) على عوائد محافظ قروض المصارف التجارية الخاصة محل الدراسة. The research aims at identifying the factors affecting the returns of loan portfolios of private commercial banks in Syria during the period (2007- 2012), where it was studying the behavior of the dependent variable represented in (Yield Loan Portfolios) and the independent variables of (employment rate of deposits in loans, the size of the bank liquidity the age of the bank, the number of branches, and the capital adequacy ratio) is studied. Research findings There is a significant positive effect for independent variables, such as age of the bank, capital adequacy ratio (except Byblos Bank Syria) affecting loan portfolios returns on private commercial banks under study. There is not a statistically significant effect for independent variables like employment rates of deposits in loans, the size of the bank, and liquidity (except Byblos Bank Syria), and the number of the bank branches (except Bank of Syria and overseas) returns on the loan portfolios private commercial banks under study.